Penerapan Etnomatematika Rumah Adat Lampung dalam Pembelajaran Bangun Datar Menggunakan Metode DDR pada Siswa Kelas III di SD - Larasaty, Lucy Amelia; Arisetyawan, Andika (Didaktika, 2021)
In the education world nowadays, it’s still common to find low results of student learning, including geometry in mathematics. Based on the observations of previous researchers, there was a didactic design error in the teacher, seen when the teacher explained the geometry material in class. This is causing the students' ability to understand geometric concepts is relatively low. Moreover, students are not familiar with the surrounding culture, including the traditional houses in their environment. The research focused on the research with third-grade students at SDN Kesugihan, with data collection using the DDR method which uses 3 stages of analysis, namely prospective analysis, metapedadidactic analysis, and retrospective analysis. Data collection begins with giving an initial learning obstacle test with 12 students as the subject. The initial didactic design designed by the researcher was compiled based on the results of the analysis of students’ books, observations, and interviews with teachers and interviews with students. The implementation of the initial didactic design was carried out with the subject of 6 students. The researcher also gave a final learning obstacle test after implementing the initial didactic design. The results obtained in this study are the reduction in the level of students learning obstacles related to conceptual errors, principle errors, and operating errors. It can be concluded that the design that has been developed by the researcher based on the analysis of the Lampung traditional house can be used by third-grade elementary school students